Ectopic Pregnancy A Clinical Casebook - Tulandi, Togas; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
Comprised exclusively of clinical cases covering ectopic pregnancy, this concise, practical casebook will provide clinicians in reproductive medicine and obstetrics/gynecology with the best real-world strategies to properly diagnose and treat the various forms of the condition they may encounter. Each chapter is a case that opens with a unique clinical presentation, followed by a description of the diagnosis, assessment and  management techniques used to treat it, as well as the case outcome and clinical pearls and pitfalls. Cases included illustrate different management strategies – from treatment with methotrexate to surgical interventions – as well as types of ectopic pregnancy, such as ovarian, interstitial, heterotopic and abdominal forms, among others. Pragmatic and reader-friendly, Ectopic Pregnancy: A Clinical Casebook will be an excellent resource for reproductive medicine specialists, obstetricians and gynecologists, and family and emergency medicine physicians alike.  .
Identification of Risk Factors of Ectopic Pregnancy -- Discriminatory Serum hCG level for Ectopic Pregnancy -- Pregnancy of Unknown Location -- Ectopic Pregnancy After In-Vitro Fertilization -- Surgical Treatment of Ectopic Pregnancy -- Bleeding Ectopic Pregnancy -- Medical Treatment of Ectopic Pregnancy -- Compliance with Methotrexate Treatment for Ectopic Pregnancy -- Inadvertent Methotrexate Administration -- Effect of Methotrexate Treatment for Ectopic Pregnancy on Current and Subsequent Pregnancy -- Interstitial Pregnancy -- Cervical Pregnancy -- Ovarian Ectopic Pregnancy -- Cesarean Scar Pregnancy --  Abdominal Pregnancy -- Intramural Pregnancy -- Heterotopic Pregnancy -- Retroperitoneal Ectopic Pregnancy -- Ectopic Molar Pregnancy -- Rudimentary Uterine Horn Pregnancy -- Fertility after Tubal Ectopic Pregnancy.
Keywords: Reproductive medicine; Gynecology .; Reproductive Medicine; Gynecology